The stability of risk level across various decision situations - Endriulaitienė, Auksė; Martišius, Vaclovas (Psichologija, 2003)
Few would dispute that we are living at a time of high anxiety and uncertainty. That’s why in recent years, social scientific interest in risk has increased enormously. The main theory that explains human decision processes in the face of risk is Prospect theory of D. Kahneman and A. Tversky. It emphasizes the impact of situation upon human risk taking. The contradictory results from the investigations in the perspective of human trait theory give the challenge to the prospect theory and raise the assumption that people have the personality trait - propensity to risk that could explain at least the part of human risky decision making and risk taking behavior. The present investigation aims to find if the decision risk level is stable across various decision situations and could be the index of human propensity to risk. The subjects were 262 students from Vytautas Magnus University and Vilnius University in Lithuania; they completed Choice Dilemma Questionnaire (Kogan, Wallach, 1964) and The Scale of General Decision Making Style (Scott, Bruce, 1995). The results showed that correlation coefficients among risk levels in various decision situations were high and significant. So risk level was stable across the situations and could be related to the personality disposition - propensity to risk. The implications of results and limitations of the study were discussed.